INOVASI PEMULIHAN EKONOMI PEREMPUAN PESISIR BERBASIS PRODUK WISATA LOKAL DESA SAWAPUDO KECAMATAN SOROPIA KABUPATEN KONAWE - Harnina Ridwan; Darmin Tuwu; Erni Qomariah; Fera Tri Susilawaty; Sarpin Sarpin; Suharty Roslan; Masrul Masrul; La Ode Muh Umran; Sirajuddin Sirajuddin; La Taya (Universitas Halu Oleo, 2022)
The post-Covid-19 pandemic has resulted in a decline in community economic activity in Southeast Sulawesi. The decline in community activities that have an impact on the economy is also felt by coastal communities, including women who live in the area. The purpose of this activity is to provide understanding to coastal women to take advantage of tourism products that can be used as a way or strategy in economic recovery after the Covid-19 pandemic. The method used in implementing the Economic Recovery Innovation of Coastal Women Based on Local Tourism Products in Sawapudo Village, Soropia District, Konawe Regency uses the lecture method and socialization to women who live in coastal areas related to the use of local tourism products to improve their economy. The results of the activity after discussions and outreach to women in the coastal area of Sawapudo village about the Innovation for Economic Recovery of Coastal Women Based on Local Tourism Products, the people who attended the socialization understood the material provided related to local tourism products in Sawapudo Village which can be marketed both offline through making posters and online through social media.